Is Neuromuscular Blocker Necessary in Pediatric Patients Undergoing Laparoscopic Inguinal Hernia Repair with Percutaneous Internal Ring Suturing? - Ahiskalioglu, Ali; İnce, İlker; Ahiskalioglu, Elif Oral; Oral, Akgun; Aksoy, Mehmet; Yiğiter, Murat; Celikkaya, Mehmet Emin; Salman, Ahmet Bedii (European Journal of Pediatric Surgery, 2017)
Purpose The aim of this study is to evaluate operating conditions during general anesthesia with or without neuromuscular blocker (NMB) in patients undergoing percutaneous internal ring suturing (PIRS).Materials and Methods In this study, 40 patients, with American Society of Anesthesiologists I and II between the ages of 1 and 12 years, were randomly assigned to two groups to receive muscle relaxant with endotracheal tube (ETT) (ETT group) or without muscle relaxant with supreme laryngeal mask airway (sLMA) (LMA group). Anesthesia was maintained with sevoflurane in oxygen (Fio2 0.3–0.5), thiopental sodium, fentanyl, and rocuronium in ETT group. In LMA group, same protocol was used without rocuronium. Heart rate, blood pressure, peak airway pressure, end-tidal carbon dioxide (EtCO2), and Spo2 were recorded before and during pneumoperitoneum maintained at a pressure of 8 to 10 mm Hg. Duration of surgery, recovery time, anesthetic time, and grade of quality view were also recorded. Airway problems (cough, hoarseness, laryngospasm, and aspiration) were recorded.Results In LMA group, there was a statistically significant reduction in recovery time versus ETT group (11.6 ± 4.08 vs. 17.15 ± 5.32 minutes; p = 0,001). There were no statistically significant differences grade of quality view between the two groups (p = 0.548). There were no statistically significant differences in oxygen saturation (Spo2), peak airway pressure, and EtCO2 between the two groups before or during insufflation (p > 0.05). Postoperative airway complications were significantly more prevalent in the ETT group. There was no case of inadequate ventilation, regurgitation, or aspiration recorded.Conclusion sLMA is safe and suitable alternative to ETT and NMB is not necessary in general anesthesia with sLMA, pediatric patients undergoing laparoscopic hernia repair with PIRS.
Keywords: percutaneous internal ring suturing; inguinal hernia repair; neuromuscular blocker; supreme laryngeal mask airway; endotracheal tube